Deprivation and Population Decline in Northern Ireland : 2017 Deprivation measures for Northern Ireland - Research Paper.: 2017 Deprivation measures for Northern Ireland - Research Paper. (2018) - Northern Ireland Statistics & Research Agency,
No abstract available